UPGRADING PENGETAHUAN MASYARAKAT TENTANG BUDIDAYA LARVA MAGOT UNTUK PAKAN LELE BERNUTRISI TINGGI MELALUI PROGRAM KKN TEMATIK DI DESA NGESREP BOYOLALI - Anvorismasra, Rizky Presla; Pujianingsih, Jingga Pramesti; Safitri, Salmaa Alyyapramuditya; Simangunsong, Elise Pinio Elsada (MAJU : Indonesian Journal of Community Empowerment, 2025)
The issue of organic waste management in Ngesrep Village, Ngemplak District, Boyolali Regency, remains a challenge as most household waste has not been utilized optimally. This condition has the potential to cause environmental pollution if not properly addressed. In response to this problem, a Community Service Program (Kuliah Kerja Nyata/KKN) was conducted in July–August 2025 with the aim of introducing maggot cultivation as an alternative solution for organic waste management as well as an economical source of animal feed. The activities included local potential surveys, counseling on the benefits of maggot cultivation, hands-on practice in maggot rearing, and evaluation of community participation. The results showed that the community gained new knowledge about utilizing organic waste into something of economic value, along with practical skills in maggot cultivation. Thus, this KKN program not only supported environmental management but also opened sustainable business opportunities with the potential to improve community welfare